CHARACTERISTICS OF ADHESION AND PROLIFERATION OF MOUSE NIH/3T3 FIBROBLASTS ON THE POLY(3-HYDROXYBUTYRATE-CO-3-HYDROXYVALERATE) FILMS WITH DIFFERENT SURFACE ROUGHNESS VALUES - V.А. Surguchenko; А.S. Ponomareva; А.Е. Efimov; Е.А. Nemets; I.I. Agapov; V.I. Sevastianov (Вестник трансплантологии и искусственных органов)
Adhesion and proliferation of NIH/3Т3 mouse fibroblasts on the surfaces of bacterial copolymer poly(3-hydroxy- butyrate-co-3-hydroxyvalerate) films with different roughness was investigated. Atomic force microscopic analysis showed that surface roughness values of all films were significantly greater (92.0 ± 7.0; 290.8 ± 7.0; 588.8 ± 16.0 nm) than that of the cultural plastic control (9.5 ±0.6 nm). It was revealed that adhesion and metabolic activity of the cells decreases with the increase of surface roughness values. NIH/3Т3 mouse fibroblasts attached weakly to the surface of copolymer films and washed away the substrate during rinsing and staining.